52.9k views
4 votes
Pre-Image PointsA (-5,-1)B (-4,2)C (0,-1)Coordinate Rule(x,y) → (x, 3y)

1 Answer

7 votes

First, I will just rewrite the points


\begin{gathered} A=(-5,-1) \\ \\ B=(-4,2) \\ \\ C=(0,-1) \end{gathered}

The coordinate rule is


(x,y)\rightarrow(x,3y)

which means we will take all the y-coordinate of the points and multiply by 3, then


\begin{gathered} A^(\prime)=(-5,3\cdot(-1)) \\ \\ B^(\prime)=(-4,3\cdot2) \\ \\ C^(\prime)=(0,3\cdot(-1)) \end{gathered}

The result will be


\begin{gathered} A^(\prime)=(-5,-3) \\ \\ B^(\prime)=(-4,6) \\ \\ C^(\prime)=(0,-3) \end{gathered}

If we plot those points we can see the figure:

In orange, we have the pre-image figure and in blue the image.

Pre-Image PointsA (-5,-1)B (-4,2)C (0,-1)Coordinate Rule(x,y) → (x, 3y)-example-1
User Whitecat
by
4.6k points